ANALISIS PERAMALAN PENJUALAN DENGAN METODE LEAST SQUARE PADA WAROENG CIKUL - Kiki Agisni; Nanda Ayu Yuliani; Ajeng Puspita Dewi; Sri Rahayu; Yuni Novalini Rahayu; Dian Hakip Nurdiansyah (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2022)
Purpose: of this research is to compare the company's sales budget with the sales budget based on least squares. Methods: The research approach used in this research is quantitative using primary data. The survey method was used for the measurement process and data collection. Through direct interviews with the parties directly involved in this research. Data Analysis: The type of data analysis used is least squares. Results and discussion : Sales of Cimol Kuah products increased. This number increased by 22,750 from 22,050 which was the company's management sales calculation. Based on the results of the correlation analysis, the correlation value (R) = 0.915 or 92% according to the least squares method, showing a strong correlation, indicating that sales of Cimol Kuah products have a very strong increasing impact. The correlation is very strong for the correlation value 0.70. Conclusion: Company management should use least squares when making sales forecasts. Because this method describes the numbers in calculations in great detail, it prevents data entry errors, makes the data more accurate, and reduces the time it takes to calculate sales.